Sensory determinants of the autonomous sensory meridian response (ASMR): Understanding the triggers - Barratt, E; Spence, C; Davis, N (PeerJ, 2017)
The autonomous sensory meridian response (ASMR) is an atypical sensory phenomenon involving electrostatic-like tingling sensations in response to certain sensory, primarily audio-visual, stimuli. The current study used an online questionnaire, completed by 130 people who self-reported experiencing ASMR. We aimed to extend preliminary investigations into the experience, and establish key multisensory factors contributing to the successful induction of ASMR through online media. Aspects such as timing and trigger load, atmosphere, and characteristics of ASMR content, ideal spatial distance from various types of stimuli, visual characteristics, context and use of ASMR triggers, and audio preferences are explored. Lower-pitched, complex sounds were found to be especially effective triggers, as were slow-paced, detail-focused videos. Conversely, background music inhibited the sensation for many respondents. These results will help in designing media for ASMR induction.